Neurocognitive Predictors of Response to Intervention With GraphoGame Rime - Wilson, Angela; Ahmed, Henna; Mead, Natasha; Noble, Hannah; Richardson, Ulla; Wolpert, Mary A.; Goswami, Usha (Frontiers in Education, 2021)
This study explores the neurocognitive predictors of response to intervention with GraphoGame Rime, an adaptive software game designed to aid the learning of English phonics. A cohort of 398 children (aged 6 – 7 years) who had participated in a recent Randomized Controlled Trial (RCT) of GraphoGame Rime in the United Kingdom were studied. Half were randomly assigned to play GraphoGame Rime (GG Rime) and the other half were assigned to Business As Usual (BAU). A series of pretests were given prior to the intervention to all participants, designed to measure phonological awareness skills, executive function (EF) skills and the ability to synchronise finger tapping to a rhythmic beat. Finger tapping is thought to provide a proxy measure of neural rhythmic synchronisation, relevant to speech encoding and developing phonological awareness. Individual differences prior to the intervention in all three types of measure were significantly associated with progression through the game. Gender was also important for progression through the game, with boys progressing significantly further than girls. Playing time, rhythmic synchronisation, phonological skills and EF skills did not differ by gender. Once playing time and non-verbal cognitive ability were controlled, phonological awareness, EF, rhythmic synchronisation and gender all remained significant predictors of progression through the game. In further analyses comparing these predictors and their interactions, and analyses controlling for the autoregressor of prior responsiveness to phonics instruction, only phoneme awareness and EF skills remained significant unique predictors. There were no significant interactions between any neurocognitive predictor. Analyses with the whole cohort (combining BAU and GG children) showed that all neurocognitive measures were significant predictors of progress in reading and spelling over the school year. We conclude that individual differences in phonological skills and EF skills predict which children will benefit most from computer assisted reading interventions like GG Rime. Further, boys appear to respond better to this computerised intervention than girls. Accordingly, to be maximally beneficial to poor readers, the supplementary use of GG Rime in addition to ongoing classroom literacy instruction could be especially targeted to boys, but should be accompanied by a focus on developing oral phonological awareness.